Policyholder protection for insurance companies with default claims: comparative analysis in Indonesia and the UK - Pradana, Alif Widhi (Universitas Muhammadiyah Magelang, 2021)
The condition of insurance in Indonesia can be categorized as wildly chaotic because the rights of insurance policyholder cannot be secured by Indonesian insurance company. Jiwasraya and Bumiputera default case is clear evidence of the incompetence insurance company in managing insurance business in Indonesia. As a comparison, United Kingdom capable to manage insurance industry and be able to protect the rights of insurance policyholder. This study aims to compare the protection of insurance policyholders in Indonesia and the United Kingdom. The research method that is used in this study is a normative research method through a comparative way that compares two different legal systems. This study is carried out through a qualitative approach. This study's results are that Indonesia and the United Kingdom have similarities and differences in the protection of insurance policyholders. Through Law number 40 of 2014 concerning insurance and Financial Services Authority (OJK) decision regulation, Indonesia has governed the provision of insurance policyholder protection in the insurance company's condition failed to pay an insurance claim. The mechanism is by using Financial health Planning and Insolvency procedures through the bankruptcy of an insurance company that is regulated under Law no 37 of 2004. Whereas, in the United Kingdom, the legal basis of insurance policyholder protection is Financial Services and Market Act. FSCS must secure insurance claims when the insurance company has a financial problem paying insurance claims toward the policyholder.